New beginnings - Anderson, Laurie Halse (Vet volunteers, 2012)
"Meet Jules and Josh, the new twins in town! While Josh adapts quickly to Ambler, Jules accidentally makes an enemy of Maggie. Hoping a pet will help her feel better, Jules adopts the class rabbit, Chewie, but things go downhill when there are complications with Chewie's spay surgery. With Dr. Mac out on a call, it's up to Jules to work with Maggie to help the rabbit - and maybe even prove that she and Josh are worthy of becoming Vet Volunteers."--